Pooled safety analysis of evolocumab in over 6000 patients from double-blind and open-label extension studies - Toth, P; Descamps, O; Genest, J; Sattar, N; Preiss, D; Dent, R; Djedjos, C; Wu, Y; Geller, M; Uhart, M; Somaratne, R; Wasserman, S; et al. (American Heart Association, 2017)
Background—Evolocumab, a fully human monoclonal antibody to PCSK9, markedly reduces LDL-C across diverse patient populations. The objective of this study was to assess the safety and tolerability of evolocumab in a pooled safety analysis from phase 2 or 3 randomized and placebo or comparator-controlled trials (integrated parent trials) and the first year of open-label extension (OLE) trials that included a standard-of-care control group. Methods—This analysis included adverse event (AE) data from 6026 patients in 12 phase 2 and 3 parent trials, with a median exposure of 2.8 months, and of those patients, from 4465 patients who continued with a median follow-up of 11.1 months in two OLE trials. Adverse events were analyzed separately for the parent and OLE trials. Overall AE rates, serious AEs (SAEs), laboratory assessments, and AEs of interest were evaluated. Results—Overall AE rates were similar between evolocumab and control in the parent trials (51.1% vs 49.6%) and in Year 1 of OLE trials (70.0% vs 66.0%), as were those for SAEs. Elevations of serum transaminases, bilirubin and creatine kinase were infrequent and similar between groups. Muscle-related AEs were similar between evolocumab and control. Neurocognitive adverse events were infrequent and balanced during the double-blind parent studies (5 events [0.1%], evolocumab groups vs 6 events [0.3%], control groups). In the OLE trials, 27 patients (0.9%) in the evolocumab groups and 5 patients (0.3%) in the control groups reported neurocognitive AEs. No neutralizing anti-evolocumab antibodies were detected. Conclusions—Overall, this integrated safety analysis of 6026 patients pooled across phase 2/3 trials and 4465 patients who continued in open-label extension trials for 1 year supports a favorable benefit-risk profile for evolocumab.